The Basics of Research in Ophthalmology - Khan, M. Daud (Pakistan Journal of Ophthalmology, 2013)
The knowledge explosion that we have witnessed in the 20th and 21st century and its mind boggling impact on human civilization through rapid technological developments, owe it all to advances in reasoning leading to innovative research. Advances in medical knowledge including ophthalmic knowledge and practices are not an exception to this rule. In the early 20th century there were no strict ethical rules governing medical research. As a result of absence of such rules, during the Second World War, some basic fundamental human rights were reportedly violated. The verdict delivered by the judges against the “The doctor Trial” in 1947 lead to the development of the famous ten point Nuremberg Code.1 This Code was later modified by the World Medical Association and eventually adopted as the famous Declaration of Helsinki (DOH) in 1964.2